Germination and Establishment of Legumes After Rice Under Rainfed Rice Systems: A Review of Literature - Agustina Asri Rahmianna (Buletin Palawija, 2007)
Crop establishment that occurs during the first three weeks of the growing phase depends on the success of seed germination and seedling emergence. As the first process, germination can be obtained only when the seed absorb water at a sufficiently rapid rate to reach minimum or critical water content, before other biotic factors can prevent its completion. In this regards, high quality of seeds is an ultimate prerequisite. It is recognized that germination and crop establishment are dominated by physical processes and therefore soil physical properties around the seed and the very young seedling govern the success. Strictly speaking, seed germination and early crop establishment are a function of soil physical condition and seed quality. A rainfed rice ecosystem is essentially a rice field with rainfall as the main source of water to flood the field prior to and during the period of paddy rice growth. This ecosystem is characterized by a lack of water control and therefore flooding and drought are potential problems. About 70 to 75% of the rice farms in Asia are rainfed due to inadequate irrigation systems. Since rice has limited success if planted after the wet season without any irrigation, farmers cultivate upland crops in lowland areas after rice that capable of coping with the dry soil during the later part of the growing season as well as to obtain additional income to support their families. Legumes are the most popular dry season crops in rainfed lowland rice-based cropping systems, as farmers expect the crops to rely on stored water left after rice. In reality, the performance of legume crops in rainfed lowland rice-based cropping systems is generally poor. It should be remembered that puddling of the soil in flooded rice fields is an integral part of rice farming in Asia. This results in waterlogged soils and poor soil physical conditions after rice, lead to the compacted and hard soils following drying. These waterlogged conditions and hard soil, together with low seed quality and fungal attack, significantly affect germination and emergence of legume crops. To obtain high crop establishment, farmers manipulate the soil physical conditions using several practices such as soil tillage, build ditches with the various levels of success.